Characterization of five associations of F8 missense mutations containing FVIII B domain mutations. (25th February 2016) - Jourdy, Y.; Nougier, C.; Roualdes, O.; Fretigny, M.; Durand, B.; Negrier, C.; Vinciguerra, C.
Abstract : Introduction: Haemophilia A (HA) is a bleeding disorder due to an absence or a reduced activity of coagulation factor VIII (FVIII) caused by mutations in F8 gene. Missense mutations represent approximately 45% of the reported molecular defects in HA. However, only few missense mutations in FVIII B domain have been described. Aim: The aim of this study was to characterize five genetic variations (three novels and two previously reported) localized in the FVIII B domain. In all cases, an additional missense variation located outside the FVIII B domain was found. We investigated each of these variations separately and in combination too for their contribution to HA phenotype. Methods: F8 variants were transiently expressed in COS‐1 cells. Media and cell lysates were collected after 72 h. Then, FVIII activity, secretion and thermostability were analysed and compared to FVIII wild‐type. Results: The 5 FVIII B domain variants showed normal FVIII:C (98.5–128.5%) and FVIII:Ag (97.7–154%). No synergistic effect was observed between the B domain variant and their associated mutations. In contrast, the variants located outside the B domain, p.V682L, p.S714L, p.V592D and p.C573F revealed significantly decrease of FVIII:C with values in the range 3.5–44.5% ( p < 0.05). However, the p.G224R variant showed FVIII:C and FVIII:Ag values no significantly different from FVIII‐WT. Conclusion: The FVIII B domain variants, p.D963N, p.S806T, p.G873D, p.H998Q and p.Q1225R may be considered as polymorphism or non‐pathologic mutations. In five patients, clinical phenotype could be explained by the additional causative missense mutation. For the p.G224T variant further splicing studies are necessary to determine its pathogenicity.